THE ROLE OF SMALL AND MEDIUM ENTERPRISES IN CONSOLIDATING THE ENVIRONMENTAL DIMENSION OF SUSTAINABLE DEVELOPMENT IN ALGERIA - Lamine Abdelhamid (International Journal of Innovative Technologies in Social Science, 2024)
The article aims to address the legal provisions Imposed by the Algerian legislature on small and medium enterprises to preserve the Environment in order to achieve the requirements of sustainable development occupies a large part of concerns in various aspects ,especially legal and public policies of environment dimension for the benefit of society in order to promote it to what is best in meeting its needs and balancing the present and future generations ,because the environment is an essential element of human life. In the context, Algerian legislator has enacted legal mechanisms for the protection of the environment, which are complied with by the small and medium enterprises, which have received special attention from the state in recent time As the main axis for sustainable development in light of the successes achieved in various economies of the countries that have worked to encourage the establishment of these institutions and provide them with various mechanisms of support and assistance. What legal obligation did the Algerian legislator have for SMES to protect the environment in order to meet the requirement of sustainable development given the support it has given him?